2023
DOI: 10.3390/en16104021
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Energy Efficiency of Public Utility Buildings in Poland through Thermomodernization and Renewable Energy Sources—A Case Study

Abstract: Economical and efficient use of energy is promoted around the world as a model of conscious care for the environment in which we live. A mere change of habits in the use of energy can reduce its costs by 5% to 15%, and investments in energy-saving technologies can pay for themselves after just a few years. This case study shows how significant steps can be taken in saving energy in the building of public utility buildings through deep thermomodernization using renewable energy sources—compressor heat pumps and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…In recent years, the emphasis on energy-saving retrofits for educational buildings has gained significant traction [20][21][22][23]. A case study for a thermos-modernization of a school in Poland [24] reported significant energy savings. The building's heat consumption was reduced by 60%, its electricity consumption was reduced by 45%, and its hot water consumption was reduced by 75%.…”
Section: School Case Studiesmentioning
confidence: 99%
“…In recent years, the emphasis on energy-saving retrofits for educational buildings has gained significant traction [20][21][22][23]. A case study for a thermos-modernization of a school in Poland [24] reported significant energy savings. The building's heat consumption was reduced by 60%, its electricity consumption was reduced by 45%, and its hot water consumption was reduced by 75%.…”
Section: School Case Studiesmentioning
confidence: 99%
“…In publications on the impact of thermal modernization on energy savings in buildings of various types in the last 2-3 years, the results of energy efficiency improvements with the use of thermal modernization are most often presented in the works [24][25][26], along with the use of modernization of conventional heat sources with the use of renewable sources of energy, e.g., in hybrid systems [26][27][28]. An assessment of real energy effects was made on the basis of measurements carried out during the 4-year period of operation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Table 3. Thermal parameters of external partitions before modernization against the technical requirements for buildings from the 2017 year (TC2017) and 2021 year (TC2021) (own elaboration based on [25,35,44]). The calculations were made in accordance with the PN-EN ISO 13790 standard and the methodology contained in the regulation of the Minister of Development and Technology of 15 December 2022 amending the regulation on the detailed scope and forms of energy audits and partial renovation audits, templates of audit cards, as well as an algorithm for assessing the profitability of a thermomodernization project.…”
Section: Energy Auditmentioning
confidence: 99%
See 2 more Smart Citations